2017
DOI: 10.1155/2017/8308612
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Activation Temperature on the Structural Properties of the Activated Carbon Xerogels and Their Electrochemical Performance

Abstract: The effect of activation temperature on the structural properties and the electrochemical performance of KOH-activated carbon xerogel was investigated in range of 700 to 1000 ∘ C. At a high temperature (1000 ∘ C), the chemical activation regenerated a more crystalline network structure of activated carbon xerogels, which was observed by Raman, XRD, and TEM images. Additionally, SEM images, BET, BJH, and -plot were used to study the structural properties of carbon xerogels. The carbon xerogel sample activated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Increasing the activation temperature reduces the activated carbon yield due to lignin incineration in biomass and the release of more volatile compounds [ 128 ]. Increasing activation temperature also increases narrow micropores and widens the established micropores using activating chemicals due to the melting of compounds found in biomass [ 129 ]. Most of the previous studies supported this statement in their research papers.…”
Section: Methods Of Biomass Activation For the Synthesis Of Acmentioning
confidence: 99%
“…Increasing the activation temperature reduces the activated carbon yield due to lignin incineration in biomass and the release of more volatile compounds [ 128 ]. Increasing activation temperature also increases narrow micropores and widens the established micropores using activating chemicals due to the melting of compounds found in biomass [ 129 ]. Most of the previous studies supported this statement in their research papers.…”
Section: Methods Of Biomass Activation For the Synthesis Of Acmentioning
confidence: 99%
“…Temperature activation of the powders under study was carried out using a solid-state thermostat for 15 min at 37 ˚C [38,39].…”
Section: D-ls-methodsmentioning
confidence: 99%
“…One important observation is that the surface area and pore volume increased from pretreated WS to WS-g-PMMA. Temperature plays a major role in defining the porous structure of biomass material (Daud et al 2003;Lee et al 2014;Quach et al 2017). Many studies have reported the increase in BET surface area and pore volume at higher reaction temperatures involving steam due to expansion/coalescence of the existing micropores to form macropores and also the simultaneous formation of new pores (Daud et al 2003;Zhao et al 2017;Ding et al 2020).…”
Section: Surface Area and Porosity Of Pristine Pretreated And Ws-g-pmmamentioning
confidence: 99%